3-(2-Bromophenyl)thiazolo[3,2-a]benzimidazole - Wang, Zhi-Ming (International Union of Crystallography, 2011)
The title compound, C(15)H(9)BrN(2)S, was prepared by the reaction of 1-bromo-2-(2,2-dibromovinyl)benzene with 1H-benzo[d]imidazole-2(3H)-thione. The thiazolo[3,2-a]benzimidazole fused-ring system is nearly planar, the maximum atomic deviation being 0.049 (4) Å. This mean plane is oriented at a dihedral angle of 71.55 (17)° with respect ot the bromophenyl ring. π–π stacking is observed in the crystal structure, the centroid–centroid distance between the thiazole and imidazole rings of adjacent molecules being 3.582 (2) Å.